Analisis Bibliometrik : Larva BSF dalam Biokonversi Limbah Organik dan Penggunaan Rasio Pakan - Annisa Yumna Azzahro; Sri Sumiyati; Badrus Zaman (Jurnal Penelitian Pendidikan IPA, 2026)
The increasing organic waste generation in line with population growth requires sustainable management solutions. Black Soldier Fly (Hermetia illucens) larvae are a promising innovation as they can convert organic waste into animal feed and fertilizer with economic value. This study aims to analyze global research trends in bioconversion by considering feed ratio using Systematic Literature Review (SLR) and Bibliometric Analysis (BA) approaches. Data obtained from Scopus for the period 2020-May 2026 May 3, 2026 were analyzed using VOSviewer for 281 publications. The results show a significant increase in the number of publications. The subject area dominated by Agricultural and Biological Sciences. Relevant journals include Animal, Poultry Science and Journal of Insect as Food and Feed. The most productive authors there is Biasato,I., (12 publication with 203 total citation). Meanwhile, Italy is the country with the highest output. The most prominent keywords are Larva. The research focuses on the efficiency of converting waste materials into environmentally friendly protein sources.